Group Communication of Combined Farmer Groups Regarding Fertilizer Supply - Mirwan; Kamaluddin Tajibu; Abd Halik (Jurnal Mercusuar, 2022)
This research aims to analyze the communication process of joint farmer groups in the preparation of the Group Definitive Needs Plan in the Biringbulu Sub-District of Gowa Regency, and to uncover the supporting and inhibiting factors in the communication process of joint farmer groups regarding fertilizer provision in the Biringbulu Sub-District of Gowa Regency.This study uses a qualitative descriptive approach, and the research type employed is a case study located in the Biringbulu Sub-District of Gowa Regency. The data sources for this research are the chairman of the Farmer Group (Gapoktan) and eight members of Gapoktan. Data collection methods employed in this research include observation, interviews, and documentation. The research instrument in this study is the researcher himself. Data processing and analysis are conducted in three stages: data reduction, data presentation, and drawing conclusions.The results of this study show that the communication process of joint farmer groups in the preparation of the Group Definitive Needs Plan involves three processes: 1) Planning process in the preparation of the plan. 2) Gapoktan evaluates the matters communicated with group members to assess the progress of the plan's preparation. 3) The chairman and group members make decisions through deliberation and consensus. Supporting factors in the plan preparation process encompass three factors: 1) Openness of Gapoktan members in conveying information. 2) Language usage and cultural similarity. 3) Use of sign language to convey information. Inhibiting factors in the plan preparation communication process involve six factors: 1) Lack of contribution. 2) Limited openness among some Gapoktan members. 3) Age factor. 4) Limited knowledge among some Gapoktan members. 5) Limited experience among some Gapoktan members. 6) Differences in character.